Secuencias de 658 pares de bases (fragmento barcode) del gen citocromo c oxidasa subunidad I (COI) de mosquitos Culex (Culex) de Córdoba, Argentina - Branda, Maria Florencia (2023)
The subgenus Culex L. includes species involved in summer–autumn arbovirus transmission but studies during winter are scarce in temperate Argentina. Female specimens were collected host-seeking at dry-icebaited traps during autumn–winter–spring at two sites in Córdoba City during 2016 and 2017. The specimens were morphologically identified and dissected to determine the follicular developmental stage (gonotrophic activity). Females with advanced follicular stages (≥III) were subjected to molecular procedures to confirm or re-identify previous morphological identification. Five species (Culex apicinus Philippi (Diptera: Culicidae), Culex dolosus (Lynch-Arribálzaga) (Diptera: Culicidae), Culex maxi Dyar (Diptera: Culicidae), Culex pipiens pipiens L. (Diptera: Culicidae), and Culex quinquefasciatus Say (Diptera: Culicidae)) were collected and found gonoactive during winter; showing that a high proportion of Culex (Culex) females remain reproductively active during the unfavorable season for mosquito populations. Among them, it is worth noting the collection of Cx. quinquefasciatus, vector of the St. Louis encephalitis virus (endemic in the city), a specimen of Cx. p. pipiens, and a hybrid of Cx. p. pipiens/Cx. quinquefasciatus (during autumn). The study of this community during winter should continue because a high gonoactive female proportion with advanced follicular stages was found: 29.12 and 13.07% in 2016 and 2017, respectively. Local studies such as this one provide evidence about ornithophilic Culex species with active year-round life cycles, species that could favor arbovirus overwintering.